Algorithms, critical pathways, and computer software for wound care: contemporary status and future potential. - Beitz JM; Bates-Jensen B (Ostomy Wound Management, 2001)
The contemporary use of algorithms, critical pathways, and computer software significantly affects all aspects of healthcare treatment from primary care to acute trauma management. Guidelines and heuristic devices specific to chronic wound care have been introduced to assist with quality implementation and monitoring of outcomes in a cost-conscious American healthcare system. Some wound care algorithms and critical pathways even have been computerized. This article discusses the differences among the various forms of wound care heuristic methods, describes their advantages and disadvantages, and suggests how they can be successfully implemented in clinical practice settings. Directions for future research also are offered.